HOW EFFECTIVE ARE CAMPUS MENTAL HEALTH SERVICES IN ADDRESSING STUDENT NEEDS? - Khosiyat Khafizova; Fozilbek Orzibekov (TADQIQOTLAR, 2025)
The Abstraction Mental health problems are becoming more and more prevalent among college students, which has an impact on both their general health and academic performance. This study addresses significant issues that impact students’ mental health, including access to services, technological treatment, and peer support groups. This study believes that a multidisciplinary program that is student-focused is essential, based on previous research and an analysis of current university mental illness programs. Evidence suggests that integrating technology-based therapy, teaching, and making sure it is as accessible as possible can greatly improve students’ mental health outcomes. All things considered, some of the most successful and long-lasting mental health techniques are those that are widely used in colleges.